Sistem Pendeteksi Banjir Berbasis Sensor Ultrasonik Hc-Sr04 Dan Modul Esp8266-12e Dengan Media Komunikasi Telegram Dan Buzzer - Hanan Hanan; Anak Agung Ngurah Gunawan; Made Sumadiyasa (Kappa Journal, 2021)
It has been designed the water surface level detection system based on the ultrasonic sensor HC-SR04 and the ESP8266-12E module through telegram and  buzzer  communication  media..  The  research  aims  to  design  a    water surface-level detection system by using ultrasonic sensors and the ESP8266-12E  module. The tools and materials used  during the design  are:   Ultrasonic sensors HC-SR04, module ESP8266-12E, and buzzer as an output to sound the alarm. The ultrasonic HC-SR04 sensor will detect the water surface level,    the detection data will be sent to the ESP8266-12E module, then the system will send the information in the form of a message through telegram and buzzer application.  The  messages  delivered  are  several  stages  including  standby, alert,  and  danger.  The  methods  used  in  this  design  are  planning,     study libraries,  collection  of  tools  and  materials,  hardware  plan,  and    program creation on the software. The final result is a system capable of detecting water surface level based on the ultrasonic sensor  HC-SR04 and the    ESP8266-12E module through telegram and buzzer communication media. The success    rate of this tool system at several stages among others at a standby of 77%, at a level of alert of 70%, and the level of success at the hazard level is 83%.